Frequency/Wavelength as the Characteristics of Black Holes - Dipo Mahto; Rakesh Paswan; Santosh Kumar (New Insights into Physical Science Vol. 12, 2021)
A model for the wavelength/frequency of Hawking radiation emitted by non-spinning black holes in terms of the radius of event horizon \((λ=8π R_s & v=c/8π R_s\)) is proposed using quantum theory of radiation ( \(E=h u)\), energy of Hawking radiation and the radius of event horizon of non-spinning black holes ( \(R_s=2GM/c^2)\). This can be used as the characteristics of non-spinning black holes. Data for the frequencies and wavelengths of Hawking radiation emitted from black holes have been calculated with the help of rest masses for stellar-mass black holes (M 5-20 MO) in X-ray binaries and for the super massive black holes (M 106 – 109.5 MO) in active galactic nuclei using the model given by \(λ=8π R_s & v=c/8π R_s\) of the research work entitled: Frequency of Hawking radiation from black holes by Mahto et al.(Dec.2013). The astrophysical objects emitting the radiations of frequencies (8.092x102Hz to 2.023x102Hz) or wavelengths (3.707x105 m to 14.828x105m) in X-ray binaries and frequencies ( 4.046X10-3Hz to 0.809X10-6Hz) or wavelengths (7.414X1010m to 37.070X1013m) in active galactic nuclei may be classified as non-spinning black holes. These frequencies or wavelengths may be regarded as the characteristics of black holes in addition to the mass, spin and charge.